Effect of bismuth substitution on magnetic properties of CoFe2O4 nanoparticles: Study of synthesize using coprecipitation method - Didik Eko Saputro; Utari Utari; Budi Purnama (Journal of Physics: Theories and Applications, 2019)
Abstract: The effect of bismuth ion substitution on the magnetic properties of cobalt ferrite nanoparticles was identified in this study. This method used in this study was coprecipitation method using 0.1 bismuth ion concentration. The results on hysteresis loop showed that the saturation magnetization of cobalt ferrite nanoparticles decreased with the substitution of bismuth ions, but the coercive field experienced the opposite. Saturation magnetization decreased from 57.97 to 51.19 emu / g, while coercive fields increased from 0.64 to 0.84 kOe.